HUBUNGAN PENGETAHUAN DAN PERILAKU HIDUP BERSIH DAN SEHAT IBU DENGAN KEJADIAN DIARE PADA ANAK USIA 1-4 TAHUN DI PUSKESMAS SIANTAN HILIR TAHUN 2013 - ., Edwin Dermody Sirait (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Diarrhea occupies the second cause of death of below fiveyears children, most of the diarrhea cases occur in Asia and Africa. InIndonesia, especially West Kalimantan, the diarrhoea is the disease that iscaused by environment and bad habit of people instead of healthy which in2011 there was only 36,07% of Pontianak citizen do hygienic and cleanbehaviors (PHBS). Objective: analyze association of mothers knowledge,hygienic and clean behaviors with diarrhea cases on 1-4 years children atPuskesmas Siantan Hilir on May 2013. Methodology: This researh is ananalytic survey with cross sectional study. The collection of data was gottenfrom 100 mothers in Puskesmas Siantan Hilir. The result of the questioner isanalyzed using Fishers test and Kolmogorov-Smirnov test. Result: In theresult of the data collection, there are 39 repondents that have 1-4 yearschildren with diarrhea history, 63 respondents have good knowlegde, 37repondents have average knowlege, 40 respondents have good clean andhygienic lives, 51 respondents do average behaviour and 9 respondents dobad behaviour. The result of bivariate analysis about association of mothersknowlegde in doing clean and hygienic behaviours (PHBS) with diarrhea onchildren is p=0,000 and the association of mothers clean and hygienicbehavior (PHBS) of mothers with diarrhea cases on children is p=0,000.Conclusion: There is significant association between mothers knowlege,clean and hygienic behaviors (PHBS) with diarrhea cases on 1-4 yearschildren at Puskesmas Siantan Hilir.Keywords: Diarrhea, Knowlegde, Clean and Hygienic Behaviors (PHBS)Notes: 1. Medical School, Faculty of Medicine, University of Tanjungpura,Pontianak, West Kalimantan2. Department of Nutrition, Faculty of Medicine, University ofTanjungpura, Pontianak, West Kalimantan3. Department of Parasitology, Faculty of Medicine, University ofTanjungpura, Pontianak, West Kalimantan